Making Education Equitable in Rural China through Distance Learning - McQuaide, Shiling (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
The Distance Education Project for Rural Schools (DEPRS) was implemented by the Chinese government between 2003 and 2007 to improve the quality of basic education in rural areas of China, especially in the poorer western provinces. It has been referred to as “the largest ICT project in the world up to now” because “it serves a larger population than any other similar projects and therefore will likely start a far-reaching information revolution in China.” This paper offers a descriptive analysis of the effectiveness and impact of DEPRS, explaining how and why it was implemented as a solution to close the wide gaps in access to high quality basic education. Focusing on the initial achievements of DEPRS, this paper explores if, how, and to what extent the three learning tools employed in DEPRS have improved basic education in remote rural areas.